Aktivitas Analgesik Ekstrak Etanol Daun Pucuk Merah (Syzygium myrtifolium Walp.) pada Mencit Putih Jantan (Mus musculus) - Lusi Indriani; Tri Nova Lovena; Nursyafni; Nawwar Irfan; Alfahtiah Zurlina (LPPM, Universitas Muhammadiyah Riau, 2024)
Analgesics are substances that reduce or eliminate pain without causing loss of consciousness. Traditional medicines are considered safer than synthetic drugs. One plant with potential as an analgesic is the red shoot plant (Syzygium myrtifolium Walp). This plant contains flavonoids, anthocyanins, phenolics, and triterpenoids. This study aimed to determine the analgesic activity of ethanol extract of red shoot leaves (EPM) in male white mice. The analgesic effect was obtained through the writhing test using 1% glacial acetic acid induction. Twenty male white mice were divided into 5 treatment groups, including negative control (0.5% Na CMC), treatment 1 (EPM 3.7 mg/kgBW), treatment 2 (EPM 7.4 mg/kgBW), and treatment 3 (EPM 14.8 mg/kgBW), and positive control (mefenamic acid 500 mg/70 kgBW). All mice were given treatment according to their respective groups. After 30 minutes, all mice were induced with 1% glacial acetic acid at a dose of 10 ml/kgBW intraperitoneally. Then, the number of writhes was observed every 5 minutes for 60 minutes. The average number of writhes data was analyzed using ANOVA and Tukey HSD tests. The results showed that treatment groups 2 (7.40 mg/kgBW) and 3 (14.80 mg/kgBW) showed analgesic activity in male white mice induced by 1% acetic acid. The best dose was 14.80 mg/kgBW with writhing protection of 34.74% and analgesic efficacy of 45.59% compared to mefenamic acid.